Género, drogas y políticas públicas en la Unión Europea: una contextualización necesaria - Xabier Arana; Virginia Montañés; Cristina Urios (Oñati Socio-Legal Series)
Both the gender issue and drugs public politics are a relatively recent reality in Europe. The essay provides a context for the two following articles, summarizing the EU process, the gender system and the social problem of drugs from a public politics point of view. The ambivalent juridical perspective (legal-illegal) to which certain behaviours linked to these kind of substances are subdued, has conditioned the scientific boundary of public politics related to drugs in the EU.